Neuroplasticity in visual impairments - Paulo Ramiler Silva; Tiago Farias; Fernando Cascio; Levi dos Santos; Vinícius Peixoto; Eric Crespo; Carla Ayres; Marcos Ayres; Victor Marinho; Victor Hugo Bastos; Pedro Ribeiro; Bruna Velasques; et al. (MDPI AG, 2018)
The visual acuity loss enables the brain to access new pathways in the quest to overcome the visual limitation and this is wellknown as neuroplasticity which have mechanisms to cortical reorganization. In this review, we related the evidences about the neuroplasticity as well as cortical anatomical differences and functional repercussions in visual impairments. We performed a systematic review of PUBMED database, without date or status publication restrictions. The findings demonstrate that the visual impairment produce a compensatory sensorial effect, in which non-visual areas are related to both cross (visual congenital) and multimodal (late blind) neuroplasticity.